The evolution of space organisation in Cocos Malays’ dwellings in Tawau, Sabah - Mohd Ariffin, Noor Aziah; Osri, Nurul Ain (2016)
This study in progress explores the unique anthropology and the dwelling culture of the Cocos Malays in Tawau, Sabah. Cocos Malays is a race of people from Cocos (Keeling) Islands in the Indian Ocean who emigrated to North Borneo (Tawau) in the early 1950s. Started by being slaves to the British on the islands and later becoming an independent society after Sabah joined Malaysia in 1963, the development of their ‘un-traditional’ dwelling culture is a unique one. The paper attempts to uncover the evolution of dwelling culture of the Cocos Malays from the beginning of their civilisation on the islands (from 1826) until the present. The dwellings concerned have always been designed and built by other people, and the occupants’ views were not taken into consideration. Through archival research and fieldwork data collection, the paper focuses on the evolution of Cocos Malays' space organisation in the dwellings in Tawau, Sabah.The paper indicates that the evolution of the space organisation and form of their houses are not conventional as in many cultures’. The study also inferred that the spatial organisation from their homeland of Cocos (Keeling) Island has some bearing on the spaces of their present dwelling culture.